Nahḍat al-‘Ulamā’ bay al-Bātinīyah al-Jāwīyah wa al-Taṣawwuf al-Islāmī: ‘Arḍun wa Munāqashāt - Muhammad Nursamad (Studia Islamika, 2004)
Three kebatinan "holy books", Darmogandul, Gatoloco, and Wirid Hidayat Jati, are the point of focus in the analysis of doctrinal sources. The tendency of these three texts to ridicule santri(students at Islamic boarding schools or pesantren) strengthens the impression that the Dutch colonial government used kebatinan to attack Islam. At the very least, this "cultural war" was closely linked to these texts.DOI: 10.15408/sdi.v11i2.604